Benjamin Elijah Mays, Schoolmaster of the Movement : A Biography - Jelks, Randal Maurice, 1956- (Book collections on Project MUSE., 2012)
This full-length biography of Benjamin Mays (1894-1984) chronicles the life of the man Martin Luther King Jr. called his 'spiritual and intellectual father'. Dean of the Howard University School of Religion, president of Morehouse College, and mentor to influential black leaders, Mays had a profound impact on the education of the leadership of the black church and of a generation of activists, policymakers, and educators.